BUREAUCRATIC REFORM TOWARDS A TRANSPARENT AND ACCOUNTABLE GOVERNMENT IN THE DIGITAL ERA - Andika, M.Rizki (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to analyze the process and challenges of bureaucratic reform in achieving a transparent and accountable government in the digital era. A qualitative approach was employed using a case study method on government institutions that have implemented digital public services. Data were collected through in-depth interviews, observations, and document analysis. The findings indicate that digitalization of bureaucracy positively contributes to enhancing transparency and accountability, particularly in public information access, service efficiency, and internal supervision. However, several obstacles were identified, including employee resistance, limited digital infrastructure, and inconsistent policies. Digital-based bureaucratic reform requires strong political commitment, human resource capacity development, and synergy between central and local governments. These findings highlight that digital transformation in bureaucracy is not merely a technological change, but also a shift in work culture and governance systems.